2017
DOI: 10.1016/j.jallcom.2016.12.262
|View full text |Cite
|
Sign up to set email alerts
|

The role of competing magnetic interactions on the abnormal expansion properties in manganese antiperovskites, Mn 3+x A 1−x N ( A  = Ni, Sn)

Abstract: The role of competing magnetic interactions in Mn-doped manganese antiperovskites Mn 3+x A 1−x N (A = Ni and Sn) has been explored using magnetometry and dilatometry, with particular focus on their relation to abnormal expansion properties. Rare negative magnetisation phenomena are found in zero-field-cooled conditions for both A = Sn and Ni when Mn is doped on the A site. Such behaviour is evidence of both competing magnetic sublattices and magnetocrystalline anisotropy. By comparison with other compounds wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…We will first discuss measurements performed on Mn 3 NiN at ambient pressure. The sample was prepared using a standard solid-state synthesis technique, as described previously [21]. Neutron powder diffraction data were collected on the D20 diffractometer (λ = 1.544 Å ) at ILL, France [22].…”
Section: Introductionmentioning
confidence: 99%
“…We will first discuss measurements performed on Mn 3 NiN at ambient pressure. The sample was prepared using a standard solid-state synthesis technique, as described previously [21]. Neutron powder diffraction data were collected on the D20 diffractometer (λ = 1.544 Å ) at ILL, France [22].…”
Section: Introductionmentioning
confidence: 99%
“…Further, it has been reported that the magnetic properties and crystalline lattices of antiperovskite nitrides such as Mn3XN (X = Cu, Ni, Ag, Zn, Ga, etc.) are dependent on the density of the valence electrons, and these crystals have been grown and evaluated in many ways [22][23][24][25]. In particular, the calculation and validation of antiferromagnetism in non-collinear magnetic moments of (Mn,Ni)4N, and the negative thermal expansion at the Néel temperature have been reported [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…First, Mn 2 N 0.86 was prepared as detailed in Ref. [12]. Subsequently, the Mn 2 N 0.86 precursor was ball milled and then thoroughly mixed by hand with elemental Zn (Sigma-Aldrich, 99.9% purity, 150 μm) and/or In powder (Sigma-Aldrich, 99.99% purity).…”
Section: Methodsmentioning
confidence: 99%